Expression and function analysis of crustacyanin gene family involved in resistance to heavy metal stress and body color formation in Exopalaemon carinicauda. Issue 4 (19th January 2021) - Gao, Huan; Ma, Hangke; Sun, Jinqiu; Xu, Wanyuan; Gao, Wei; Lai, Xiaofang; Yan, Binlun
Abstract: Crustacyanin has the function of binding astaxanthin which is the best antioxidant, and plays an important role in the body color variation of crustaceans. To investigate the causes of body color variation of the ridgetail white prawn, Exopalaemon carinicauda, the present study obtained four subtypes of crustacyanin gene: C1, C2, A1, and A2. Based on fluorescence quantitative polymerase chain reaction, lipocalin‐C1 is mainly expressed in the eyestalk, lipocalin‐C2 is in the ventral nerve cord, and lipocalin‐A1 and lipocalin‐A2 are in subcutaneous adipose tissues. Under the inhibiting effect of Cd 2+ stress, the expression of four subtypes first increases and then decreases within 24 h, and reaches the maximum at 6 or 12 h. RNA interference experiments showed a decrease in the expression of lipocalin genes in subcutaneous adipose tissue for each subtype, with the body color changing from transparent to red, and the dark red spots on the epidermis changing to bright red. Moreover, the blue protein in the subcutaneous adipose tissue largely disappeared, based on the light micrographs. In view of these findings, the crustacyanin gene appears to fulfill some function in the resistance to heavy metal stress and body color formation of E. carinicauda . Abstract : It is firstly reported in the crustaceans, that the reduction of crustacyanin gene expression of Exopalaemon carinicauda will change the body color from transparent to red (see figure), and the dark red spots on the epidermis also change to bright red. Moreover, the blue protein in the subcutaneous adipose tissue disappears in a large amount as the microscope image shows. Highlights: Four subtypes of the crustacyanin gene in E. carinicauda were cloned for the first time, which function were revealed to relate to the change of body color. The expression of crustacyanin gene involved in resistance to heavy metal stress.